EFFECTIVENESS OF THINK TABLE LEARNING MEDIA IN IMPROVING STUDENTS' LOGICAL THINKING ABILITIES - Fikri, Tsaqibul; Labiba Kusna, Siti; Isroani, Farida (Universitas Al-Hikmah Indonesia, 2024)
The period of development and growth in a child's life is very fundamental, children begin to be sensitive to accepting various developmental efforts, one aspect of child development is logical thinking. The results of observations made at RA Raudlatun Nashirin, Tinawun Village, Malo District, Bojonegoro Regency, showed that the achievements in the development of logical thinking in children aged 4-5 years were still not optimal, this was due to the lack of media to improve children's logical thinking abilities. This research aims to produce Think Table media products to improve logical thinking skills. The type of research used is (Research and Development) with the ADDIE development model which includes 5 stages, namely analysis, design, development, implementation. and evaluation. The trial was carried out with pre-test and post-test activities on 18 children aged 4-5 years. The product results validated by media experts received a score of 95% in the very appropriate category and material experts received a score of 97% in the very appropriate category. Meanwhile, the results of the pre-test activities got a score of 66% in the good category, the treatment activities for 2 days by stimulating children using Think Table media and the post-test activities got a score of 87% in the very good category, from the pre-test and post-test activities. tests experienced a 21% increase. Thus, Think Table media is very suitable for use by children and can improve logical thinking skills in children aged 4-5 years, Tinawun village, Malo subdistrict, Bojonegoro district.